Communicating a Health Risk/Crisis: Exploring the Experiences of Journalists Covering a Proximate Epidemic. Issue 6 (December 2019) - Thompson, Esi E.
Media are an indispensable partner in health communication, but there is often concern about how the media cover health and science issues. These critiques tend to be based on analyses of news content that don't consider the production process of the content. Using a media sociology framework, the article examines the news production process of the Ebola outbreak from the perspective of Ghanaian journalists. The study finds that existing and new routines influenced what the media produced. This study reiterates the call for public health to work closely with the media and to provide translated health information in multilingual low-literate societies.